Text in psycholinguistics: Aspectual generalizations as well as language and psycho-accentuation dimensions of artistic text of distinguished Ukrainian writers - Papish, Vitaliia (Theoria et Historia Scientiarum, 2023)
The article gives the insight into the notion of “text” via “prism” of linguistic and psycholinguistic parameters and presents its “broad” and “narrow” interpretation in humanities. It is pointed out that the linguistic parameters of the text include its in-tegrity, coherence, and boundary structuring, while psycholinguistic definitions focus on emotions and creativity of the sender and addressee. The psychological aspects and stages of text creation are analyzed with reference to knowledge of its background and linguistic presupposition. The contribution of Ukrainian and foreign studies to the development of the psycholinguistic foundations of the text are discussed on the basis of examples from Ukrainian literature. It is proved that the interdisciplinary approach to the analysis of the text is crucial for text study; the peculiarities of text creation are characterized through the opposition “generation – perception”, as well as through the expression of the linguistic personality of its ego in the text. The positive and negative impact of the text on the recipient is highlighted as well as it gives up-to-date interpretation of such notions as pathological text, apperception, understanding, interpretational variability of the text. The phenomenon of linguistic and psycho-accentuation is being analyzed on the basis of the texts of Ukrainian distinguished writers (P. Kulish, O. Kobylyanska, I. Ogienko, and others). The author characterizes the influence of linguistic and extralinguistic factors on increasing psycholinguistic accentuation.